Evaluation of Treatment of Distal Tibia Fracture with an Intramedullary Interlocking Nail and Single Poller Screw - Karki, Prateek; Ranabhat, Roshani; Shrestha, Sabin (Journal of Nepalgunj Medical College, 2023)
Introduction: Distal tibia fracture tends to angulate while using a standard intramedullary interlocking nail. By using a single Poller screw, the medullary cavity's functional diameter is reduced. This leads to angulation correction and three-point fixations, which improve the mechanical stability of the nail-bone construct.Aims: To assess the functional and radiological results of the intramedullary interlocking nail and poller screw in management of adult distal tibia fracture.Methods: All patients with distal tibia fractures age more than 18 years, treated with intramedullary interlocking nails and a single poller screw at Nepalgunj Medical College between January 2022 and April 2023 were included in this prospective study.  Radiological examination involved measuring sagittal and coronal plane angulation pre and postoperatively, while functional outcome was assessed using the Karlstorm- Olerud score. Ethical clearance was obtained from Institutional Review Committee.Results: Total 30 patients, 19 male and 11 females with mean age of 32.37 ± 11.02 (range 18 to 62 years) were treated. Mean difference of diameter between isthmus and fracture site was statistically significant. There was significant reduction in coronal and sagittal plane angulation after surgery which was maintained till union.  All fractures united at an average of 17.60 ± 2.25 weeks, with 90% having good to excellent results.Conclusion: Using a poller screw with an intramedullary interlocking nail can greatly alleviate the angulation issue with the distal fragment for distal tibia fracture.